Efektivitas Pengadilan Hubungan Industrial dalam Penyelesaian Perselisihan Perburuhan dan Perlindungan bagi Pekerja - Aryanti Agripina Winata; Gunardi Lie (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2026)
This study analyzes the effectiveness of the Industrial Relations Court (PHI) as a specialized court in handling labor disputes—such as conflicts over rights, interests, termination of employment, and disputes between labor unions—while protecting workers who are economically and structurally more vulnerable than employers, within the framework of the rule of law that upholds the supremacy of law and equality before the law. Using a normative legal approach through legislative studies and conceptual analysis based on primary sources such as Law No. 2 of 2004 on the Settlement of Industrial Relations Disputes, as well as secondary sources from legal literature. The analysis reveals that the Industrial Relations Dispute Resolution System (PHI), designed for swift, fair, and cost-effective resolution through stages of bipartite negotiation, mediation, conciliation, arbitration, and litigation as a last resort, has not yet achieved optimal results due to weak regulatory frameworks, lengthy processes, high costs, ineffective enforcement of decisions, and an imbalance in workers’ bargaining power. Systemic reform is required in the form of strengthening enforcement regulations, enhancing the capacity of expert judges, digitizing procedures, optimizing non-litigation mechanisms, and expanding free legal aid for workers to achieve substantive justice and true legal certainty.